STRATEGY DEVELOPMENT OF DAIRY FARMS BY USING SWOT ANALYSIS IN PROVINCE BENGKULU - Arief Juliansyah; Redy Badrudin; Endang Sulistyowati (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2022)
Compared to imported milk, milk production is much lower. It is necessary to create new milk producing areas outside Java, such as Bengkulu Province which is ideal for dairy farming. This study aims to determine the strategy of dairy farming in Bengkulu Province. The method used in this research is the SWOT anaysis method. Research on dairy farms in Bengkulu Province, precisely in the Districts of Kepahiang and Rejang Lebong, uses a purposive method. The research took place between October 2019 and January 2020. The sampIing technique was carried out by direct interviews with 20 respondents and two experts. The results showed that the cattle development strategy must use a strategy between strengths and weaknesses, namely an aggressive strategy. It is recommended that every stakeholder, including local government, should make an aggressive strategic plan and implement it in an effective program to increase the effectiveness of the alternative methods that have been developed. Increase the number of cattle population and expand sales of dairy products to complete the program